Development and evaluation of a new assistive device for low back load reduction in caregivers: an experimental study - Yuka Omura; Masayuki Hirata; Toshiki Yoshimine; Eiji Nakatani; Tomoko Inoue (Scientific Reports, 2022)
Abstract Low back pain among healthcare professionals is associated with the manual handling of patients. Some bed features for turning and repositioning have been developed; however, the load during patient care remains heavy. We developed a device to reduce low back load in caregivers during patient bedside care and evaluated it objectively and subjectively from a caregiver’s perspective using a randomised crossover study. Overall, 28 clinical nurses and care workers were randomly assigned to two interventional groups: administering care with (Device method) and without (Manual method) the device in an experimental room. We measured the caregiver’s trunk flexion angle using inertial measurement units and video recording during care and then defined a trunk flexion angle of > 45° as the threshold; the variables were analysed using linear mixed models. Subsequently, participants responded to a survey regarding the usability of the device. Trunk flexion time and percentage of time were 26.5 s (95% confidence interval: 14.1 s, 38.9 s) (p < 0.001) and 23.0% (95% confidence interval: 16.4%, 29.6%) (p < 0.001) lower, respectively, in the Device group than in the Manual group. Furthermore, caregivers evaluated the care they could administer with the device as being better than that associated with manual care.